AREDS2 sebagai Strategi Perlindungan Retina Terhadap Penuaan: Tinjauan Pustaka dari Perspektif Gerosains: Tinjauan Pustaka - Wilaksono, Bhirau; Elfandari, Enno; Ichsan, Rayhani; Alfiandari, Dhini; Damry, Nurul Muf'idah; Chairul, Andi Makkawaru; Aminuddin, Nurul Mutiah; Nurdin, Novi Safitri; Chandrawati, Aida Ayu; Hammado, Nurussyariah (PT Kalbe Farma Tbk., 2026)
Introduction: Age-related macular degeneration (AMD) is a leading cause of irreversible vision loss among the elderly population. The Age-Related Eye Disease Study 2 (AREDS2) supplementation was developed as an evidence-based nutraceutical strategy to slow the progression of AMD. This review aims to evaluate the clinical evidence and potential application of AREDS2 as a geroprotective retinal intervention within the framework of precision geromedicine. Methods: A narrative review of recent AREDS and AREDS2 studies was conducted, integrating concepts from geroscience related to retinal aging. Results: The AREDS2 formulation, which replaced beta-carotene with lutein and zeaxanthin, demonstrated an 18% reduction in AMD progression risk without increasing lung cancer risk among smokers. AREDS2 components target key aging pathways, including oxidative stress, mitochondrial dysfunction, chronic inflammation, and dysregulated autophagy. In addition, potential modulation of mTOR and AMPK signaling suggests a role in extending retinal healthspan. Conclusion: AREDS2 represents a promising nutraceutical approach as a retinal gerotherapy within the paradigm of precision geromedicine. Its clinical implications include preventing AMD progression, optimizing visual function in older adults, and enabling integration into precision-based ophthalmologic practice. Further research is warranted to validate the molecular mechanisms and assess the cross-population effectiveness, thereby strengthening its role in broader age-related ocular health interventions.